Development and Validation of a Female Sexual Arousal Questionnaire in Women Affected by Marital Infidelity - Aghili , Mojtaba; Yazdani, Parastoo (Journal of Assessment and Research in Applied Counseling (JARAC), 2022)
Background and Aim: Emotion seeking as a personality trait in the emotional range is a very significant issue that has tangible effects and undeniable results on interpersonal relationships and can be a corner of family relationship issues in the form of emotional relationships between two people. To make a marriage contract. Considering that there is no independent and indigenous questionnaire in our country to examine women's sexual arousal that corresponds to social and Islamic conditions, it is necessary to design and build a valid questionnaire on this issue. Therefore, the aim of this study was to validate the Women's Sexual Emotion Questionnaire in women affected by marital infidelity.  Methods: This study was a descriptive normative study. For this purpose, among the women affected by the betrayal of Bojnourd city, 200 people were selected by available sampling method and answered the sexual arousal questionnaire in women. The data were analyzed using confirmatory factor analysis and Cronbach's alpha. Results: The results showed that the Persian version of female sexual arousal in the Iranian sample has an approved factor structure. The validity of the structure was evaluated using confirmatory factor analysis, which showed that all factors had a very good fit (P